Fathering the Nation : American Genealogies of Slavery and Freedom. - Castronovo, Russ. (Berkeley : University of California Press, 2022)
Russ Castronovo underscores the inherent contradictions between America's founding principles of freedom and the reality of slavery in a book that probes mid-nineteenth-century representations of the founding fathers. He finds that rather than being coherent and consensual, narratives of nationhood are inconsistent, ambivalent, and ironic. He examines competing expressions of national memory in a wide range of mid-nineteenth-century artifacts: slave autobiogra.
Description based upon print version of record.
JSTOR
Keywords: American literature -- 19th century -- History and criticism; Slavery in literature; Enslaved persons -- Emancipation -- United States -- Historiography; National characteristics, American, in literature; Narration (Rhetoric) -- History -- 19th century; Slavery -- United States -- Historiography; United States -- Civilization; Liberty in literature; Memory in literature; Narration (Rhetoric); Littérature américaine -- 19e siècle -- Histoire et critique; Esclavage dans la littérature.; Narration -- Histoire -- 19e siècle.; Esclavage -- États-Unis -- Historiographie; États-Unis -- Civilisation; Liberté dans la littérature.; Mémoire dans la littérature.; Narration; American literature; Civilization; Liberty in literature; Memory in literature; Narration (Rhetoric); National characteristics, American, in literature; Slavery -- Historiography; Slavery in literature; United States; 1800-1899; Criticism, interpretation, etc; History